Validation of the english assessment of criteria for specific internet-use disorders (ACSID-11) for tinder and online pornography use - Liberacka-Dwojak, Magdalena; Cruz, Germano Vera; Wiłkość-Dębczyńska, Monika; Rochat, Lucien; Khan, Riaz; Mueller, Silke M.; Brand, Matthias; Khazaal, Yasser (Frontiers in Psychiatry, 2025)
Background and aimsInternet behaviors, like social networking, dating apps, or online pornography, may develop into disorders due to their addictive potential, aligning with other specific Internet-use disorders in ICD-11. This study aimed to validate the Assessment of Criteria for Specific Internet-use Disorders (ACSID-11) for Tinder and online pornography use in English-speaking respondents.MethodsThe ACSID-11 was administered to active Tinder and pornography users fluent in English (N = 1823) alongside the Problematic Tinder Use Scale (PTUS), Short Problematic Pornography Consumption Scale (PPCS-6), and Sexual Desire Inventory-2 (SDI-2). Confirmatory factor analyses (CFA) examined ACSID-11’s factor structure, and correlation analyses assessed its convergent validity. The eight-factor structure was confirmed and was superior to other tested solutions both for Tinder and online pornography use. ACSID-11 scores correlated with the PTUS, PPCS-6, and SDI-2.Discussion and ConclusionsThe ACSID-11 is a suitable tool for testing other specified disorders due to addictive behaviors such as Tinder and online pornography-use disorders, based on ICD-11 diagnostic criteria, valuable in assisting with a detailed clinical diagnosis. Moreover, the tool is also valid for English-speaking respondents